Encyclopedia of Structural Health Monitoring 2008
DOI: 10.1002/9780470061626.shm066
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for Detection of Degraded Zones in Metallic and Composite Structures

Abstract: This paper presents the state of the art of modeling and detection of damages in metallic and composite structures. The continuous, discrete‐continuous, and discrete models available in the literature are described. Also, the influence of damages on vibration behavior of structures is presented, along with possibilities of damage detection based on changes in dynamic characteristics of structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The deviation from 1 can be interpreted as a damage indicator in structures. This index is based on comparisons between the changes in the mode shapes obtained both from tests and from calculations, the MAC is defined by W. M. Ostachowicz et al 1996: (17) = Test mode shape vector. = calculate mode shape vector.…”
Section: Modal Assurance Criterionmentioning
confidence: 99%
“…The deviation from 1 can be interpreted as a damage indicator in structures. This index is based on comparisons between the changes in the mode shapes obtained both from tests and from calculations, the MAC is defined by W. M. Ostachowicz et al 1996: (17) = Test mode shape vector. = calculate mode shape vector.…”
Section: Modal Assurance Criterionmentioning
confidence: 99%
“…The GA arithmetic is often used in determining collocation of sensors. Ostachawicz [1] et al demonstrated the use of GA in damage detection using a damage index as the fitness function. Staszweski [2] et al used GA to place sensors on a grid for damage detection.…”
Section: Introductionmentioning
confidence: 99%